Gloeophyllum odoratum (Wulfen) Imazeki як індикатор корінних старовікових ялицевих лісів в Українських Карпатах - Згонник, Микола Олексійович; Zghonnyk M.О. (Львів: Галич-Прес, 2023)
The article contains information on the distribution and indicator properties of a rare species of polyporoid fungi - Gloeophyllum odoratum. Information on the protection status of the fungus in European countries is given. Information about the substrate preferences of this species is analyzed.
Gloeophyllum odoratum (Wulfen) Imazeki як індикатор корінних as an indicator of old native fir forests in the Ukrainian Carpathians
Keywords: гриби; індикатори; біорізноманіття; ялиця; Національний природний парк; Синьогора; Україна